Microbial Survival in an Extreme Martian Analog Ecosystem: Poás Volcano, Costa Rica - Wang, Justin L.; Dragone, Nicholas B.; Avard, Geoffroy; Hynek, Brian M. (Frontiers in Astronomy and Space Sciences, 2022)
Past acid-sulfate hydrothermal systems on Mars have promise in their ability to have hosted life for billions of years. One method for analyzing these systems is to study analog environments on Earth. To assess the astrobiological potential of Martian acid-sulfate hydrothermal systems, the crater lake of the active Poás Volcano, Laguna Caliente, was sampled in 2013 and 2017. Laguna Caliente presents an extremely dynamic terrestrial environment with near-ambient to boiling temperatures, pH fluctuations from -0.87 to 1.5, a wide range of chemistries and redox potential, and frequent phreatic-to-phreatomagmatic eruptions. Samples of lake fluid, sulfur clumps, and lake bottom sediment underwent 16S rRNA gene sequencing and metagenomic ‘shotgun’ sequencing, which revealed this lake hosts an extremely low biodiversity of microorganisms dominated by Acidiphilium spp. Shotgun metagenomics of the samples suggests this community has numerous genetic adaptations that confer survival, including functional pathways to reduce the effects of toxic metals and numerous metabolic pathways utilizing a variety of simple and complex sugar molecules. The identification of these various metabolic pathways suggests adaptations related to carbon limited environments, fulfillment of high energy requirements, and survival in a hostile volcanic setting. The perseverance of life in Laguna Caliente indicates life on Mars could have thrived in analogous environments, stressing the need for the search for life in relict Martian acid-sulfate hydrothermal systems.